Strategy of NPP I&C Systems’ Modernization in Ukraine - Yastrebenetsky, M.; Rozen, Yu.; Klevtsov, A.; Gashev, M. (Ядерна та радіаційна безпека, 2012)
The stages of modernization of Ukrainian NPP I&C systems are described in the paper. The first stage (1993—2000) was characterized by use of systems designed by foreign (including USA) companies. The second stage (2001—2011) was characterized by use of systems designed by Ukrainian companies. The modernization strategy is analyzed in two aspects: the strategy of operators and the strategy of I&C systems’ designers. Some features peculiar to the strategy of designers are: an aggregate of hardware, software and service apparatus called “hardware-software complex” (HSC) as central part of systems, which are delivered to NPPs in full assembly and are connected to peripheral equipment at NPP; use of FPGA for performance of safety functions; elaboration of new equipment families. The third stage starts in 2012 and is related to construction of two new units (Khmelnitsky-3 and 4). A new regulatory framework, including regulatory requirements, will be elaborated for I&C systems of these units.